Assessing the determinants of unhealthy dietary habits among a sample of survey participants in Jamaica - Althea La Foucade; Samuel Gabriel; Vyjanti Beharry; Christine Laptiste; Charmaine Metivier; T. Alafia Samuels; Karl Theodore; Patricia Edwards-Wescott (Pan American Health Organization, 2022)
Objective. To identify and assess the determinants of unhealthy dietary habits among a sample of survey participants in Jamaica. Methods. Because of resource constraints, this cross-sectional assessment is based on a three-stage non-probability sample of 374 survey respondents in Jamaica aged ≥18 years. Firstly, three administrative areas (parishes) were randomly selected. Secondly, the main commercial areas within the selected parishes were identified, from which a non-probability sample of establishments was drawn. A broad selection of establishments covering public, private, and nongovernmental organizations was chosen. This array of establishments was selected to capture a sample of respondents that was as representative as possible. Patrons and employees in the selected establishments were asked to complete a questionnaire. Results. Respondents' self-assessment of their general consumption revealed that 48.4% were unhealthy eaters. Among these, the top reasons for generally unhealthy dietary choices were greater accessibility of unhealthy foods (63.5%) and limited time to prepare healthy meals (61.3%). Additionally, 52.5% indicated "unhealthy foods cost less," and 47.0% identified affordability as the main factor in the food choice equation. Findings revealed that the determinants of eating unhealthily tended to vary across income, age, and gender. Female, younger, and lower-income respondents have a higher likelihood of being impacted by the factors. Conclusions. The largest proportions of the sample identified limited time to prepare healthy meals and the ease of access to unhealthy foods as the foremost determinants of unhealthy eating habits. These barriers to healthy eating are more likely to impact survey participants in the 18-34 age group.